2014
DOI: 10.1002/anie.201400161
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Enalcarbenoids: Direct Synthesis of Indoles by Rhodium(II)‐Catalyzed [4+2] Benzannulation of Pyrroles

Abstract: Disclosed herein is the design of an unprecedented electrophilic rhodium enalcarbenoid which results from rhodium(II)-catalyzed decomposition of a new class of enaldiazo compounds. The synthetic utility of these enalcarbenoids has been successfully demonstrated in the first transition-metal-catalyzed [4+2] benzannulation of pyrroles, thus leading to substituted indoles. The new benzannulation has been applied to the efficient synthesis of the natural product leiocarpone as well as a potent adipocyte fatty-acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…76 Formylation of the terminal alkene afforded enal diazocarbonyl compounds, precursors to unprecedented electrophilic rhodium enal carbenes. 77 Finally, a triflic acid-catalyzed Povarov reaction of alkenyldiazoesters allowed the preparation of various six-and seven-membered rings. 78 In his 2009 review, 8 Maas identified six compounds/classes of compounds as suitable scaffolds for building other diazocarbonyl compounds (Scheme 36).…”
Section: Preparation Of Vinyldiazoestersmentioning
confidence: 99%
“…76 Formylation of the terminal alkene afforded enal diazocarbonyl compounds, precursors to unprecedented electrophilic rhodium enal carbenes. 77 Finally, a triflic acid-catalyzed Povarov reaction of alkenyldiazoesters allowed the preparation of various six-and seven-membered rings. 78 In his 2009 review, 8 Maas identified six compounds/classes of compounds as suitable scaffolds for building other diazocarbonyl compounds (Scheme 36).…”
Section: Preparation Of Vinyldiazoestersmentioning
confidence: 99%
“…1006) in a process that involves C-H insertion followed by cyclization [1070] and a related preparation of carbazoles from indoles (2) ring expansion of α-diazo esters substituted by aminomethyl groups [1076]; (3) catalyst and substituent effects on intramolecular Buchner (cycloheptatriene from benzene) reactions involved α-diazo ketones [1077];…”
Section: Scheme 80 Reaction Of Heteroarylcarbene Complexes Through Cmentioning
confidence: 99%
“…Upon ring-opening, the resulting alkoxonium (or iminium) intermediate I undergoes enolate isomerization to form the Lewis acidenolate chelate complex II. Next, a Prins-type cyclization [23] occurs to form the intermediate III, which readily aromatizes by elimination of R 1 XH (X = O or NR 4 ) to form the benzofused product.…”
mentioning
confidence: 99%
“…Benzannulation is preferable due to the likely reduction of reaction steps and better control of regiochemical outcomes. The vast majority of benzannulation approaches involve [4+2], [4] [2+2+2], [5] [3+3], [6] and [6+4] [7] cycloadditions, ring-closing metatheses, [8] Danheiser annulations, [9] transition-metal-promoted processes, [10] and base-induced rearrangements.[11] Many of these methods have serious limitations that reduce their scope and applications, including: 1) the requirement of an additional oxidation step (usually 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, DDQ) to form the final aromatic ring; 2) the use of highly functionalized precursors that are challenging or not straightforward to access; and 3) the employment of highly air-or moisture-sensitive precursors. Therefore, methods involving readilyaccessible, stable precursors that directly convert to the desired benzo-fused products remain an important synthetic endeavor.…”
mentioning
confidence: 99%